Emancipation: the lessons and the legacy development of business enterprises after slavery - Churches' Emancipation Committee; Hope United Church; Boulevard Baptist Church; The United Theological College of the West Indies; Bethel Baptist Church; Meadowbrook United Church; St. Andrew's Scots Kirk United; Webster Memorial United Church
This is an invitation programme by the Churches' Emancipation Committee for their twenty first emancipation lecture and cultural presentation. The event took place on Sunday, July 27, 2014 at the Hope United Church.
Keywords: Programmes. -- Jamaica